(untitled) (New York, 2006)
Modern architecture merges the dreams and technological experience of humanity. This illustrated book examines 48 works that have changed the face of our planet. It probes a century of great constructions, seeking in these glass, steel and concrete masterpieces the very essence of our civilization, through the legacies they have left us and their extraordinary insight into our future
Keywords: Modern architecture,Kiến trúc hiện đại